2014
DOI: 10.1111/psyg.12049
|View full text |Cite
|
Sign up to set email alerts
|

Do depressive symptoms on hospital admission impact early functional outcome in elderly patients with hip fracture?

Abstract: Increasing levels of depressive symptoms in elderly hip fracture patients influence short-term functional outcome. We strongly support the introduction of routine assessment of this baseline comorbidity, especially in female patients. Failure to identify such patients is a missed opportunity for possible improvement of early functional outcome after hip fracture in elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
6
26
0
Order By: Relevance
“…As mentioned before, depression is a common condition among elderly patients with a high prevalence. The 45.8% prevalence found in this study is in keeping with results reported in other studies 2,3,25 . Likewise, Szczerbińska K. et al 26 reported twice-higher prevalence in hospitalized OA compared to OA in asylums.…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned before, depression is a common condition among elderly patients with a high prevalence. The 45.8% prevalence found in this study is in keeping with results reported in other studies 2,3,25 . Likewise, Szczerbińska K. et al 26 reported twice-higher prevalence in hospitalized OA compared to OA in asylums.…”
Section: Discussionsupporting
confidence: 93%
“…35 The presence of moderate to severe depressive symptoms is known to impact short-and long-term functional outcomes in elderly hip fracture patients. 36 In our cohort, 121 patients (30.1%) had a GDS-15 score that indicated the presence of depressive symptoms. On admission, the only significant difference found between the community-dwelling individuals and nursing home residents was a higher degree of depressive symptoms in the institutionalized participants.…”
Section: Discussionmentioning
confidence: 71%
“…While some studies have found that the presence of depression or depressive symptoms can adversely affect functional outcome after hip-fracture 76,[79][80][81][82][83] , other studies have not shown this association [84][85][86][87] , so uncertainty still exists. The evidence is conflicting, and as the question is still a moot point further investigation is warranted.…”
Section: Depression and Hip Fracturementioning
confidence: 99%
“…Study IV focused on examining the influence depression has on functional outcome and quality of life one year after hip fracture. The findings in the literature are inconclusive, as some studies have found a correlation between depression and poorer functional outcome after hip fracture 76,[79][80][81][82][83] while other studies have not established this link. [84][85][86][87] They suggest that comorbidity 86 , as well as cognitive function and fear of falling 85 affect functional outcome more than depression.…”
Section: Depression and Hip Fracturementioning
confidence: 99%